Penerapan Terapi Inhalasi Uap Sederhana dan Fisioterapi Dada untuk Menurunkan Frekuensi Nafas pada Pasien dengan Bronkhopneumonia di Ruang Ismail II RS Roemani Muhammadiyah Semarang - Astuti, Yayuk Dwi; Kartikasari, Dian; Purwati, Eny (Universitas Malahayati, 2023)
ABSTRACT Bronchopneumonia is inflammation of the small bronchial walls accompanied by atelectasis in their branching areas. Another term used to describe pneumonia where consolidation is widely distributed around the bronchi and does not have a lobar pattern. This condition begins with inflammation of the lung tissue or alveoli, usually preceded by an upper respiratory tract infection for several days. Non- pharmacological therapies to clear the airway and reduce respiratory frequency include simple steam inhalation and chest physiotherapy. This study aims to determine whether there is an influence of simple steam inhalation and chest physiotherapy on reducing respiratory frequency in patients with bronchopneumonia in Ismail II Ward, Roemani Muhammadiyah Hospital Semarang. The study accesses databases and conducts a comprehensive search on Google Scholar for articles in Indonesian language. The search is done by combining keywords: